Experimental Study of Compressive Properties and Environmental Impact of Recycled Aggregate - Xuetong, Ma; Debin, Gao (Frontiers in Materials, 2021)
As the main component of fiber-reinforced recycled aggregate concrete, the properties of recycled aggregate determine whether recycled aggregate concrete can be used in engineering applications. To study the compressive properties and environmental impact of recycled aggregate, large-scale indoor compression tests were carried out on recycled aggregate under different moisture contents, concrete aggregate ratios, dry-wet cycles, and loads.The results showed that the crushing rate and settlement first increased and then decreased upon increasing the moisture content. Upon increasing the concrete aggregate ratio, the settlement continuously decreased, and the crushing rate decreased from 157.2% to 82.5%. Upon increasing the number of dry-wet cycles, the settlement continued to increase to an upper limit of about 17.5%, and the crushing rate increased to 35%. Upon increasing the load, the settlement and crushing rate of the aggregate increased. These results show that the effects of aggregate ratio, moisture content, and dry-wet cycles on settlement were caused by crushing the aggregate. Based on this, a formula was constructed to predict the final settlement of reclaimed aggregate. The leaching amount of Cr in recycled aggregate was 0.0175–0.0375 mg/L under normal conditions, but under extreme conditions, the leaching amount of some sampling points was greater than in the standard requirements. This means that recycled aggregate may pose environmental risks that should be mitigated during use. Recycled aggregate can be used to construct sponge city storage and reuse facilities, as well as fiber-reinforced recycled aggregate concrete, but its sources need to be determined to ensure that it does not pose environmental risks.